LIFELONG LEARNING POLICIES IN VARIOUS COUNTRIES: THE NORTH vs THE SOUTH An adult educator’s view - Keja-Kaereho, Charlene (IJRDO- Journal of Educational Research, 2016)
This paper focuses on the discussion of Lifelong Learning Policies of variouscountries. Concentration will be paid on the policies recommendations,evaluations done and examples at community level.